A study of the self-diffusion of certain of the lower alkyl halides - Stein, Louis Henry (Department of Chemistry, 2016)
The self-diffusion coefficients of Mel, and Et-, nPris-,isoPr-, nBu-, isoBu- and secBu-iodides and bromides were determined by application of the capillary tube method and using iodine-131 and bromine-82 for labelling the compounds. Viscosities were measured for those compounds for which the data in the literature were insufficient for calculation of energies of activation. The diffusion coefficients were of the order of 2 x 10⁻⁵ cm².sec⁻ with activation energies of 2 kcal./mole; determined from plots of log D/T versus l/T. The temperatures at which coefficients were measured were 7.35, 19.35 and 30.00° C. The activation energies measured agreed with those for viscous flow as is required by the theories of Frenkel and Eyring.